METHODOLOGY OF QUANTITATIVE ESTIMATION OF THE ORGANIZATION MISSION STATEMENT - Anatoly V. Kolesnikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides the author’s research approach, which orients to the audience whose thinking processes are shaped in the midst of resolving everyday technical tasks. The author puts forward an algorithm of quantitative estimation of the company mission statement accompanied by visualization of the result through a petalled diagram. This approach provides higher interest of learners in studying outcomes, as it coincides with the usual way of thinking processes. The article presents parameters of the company mission statement and the procedure of their conversion to quantitative figures. This methodology can build a foundation for comparing, analysis and estimation of the company standing in market and prospects of its development.